Submarine rescue decompression procedure from hyperbaric exposures up to 6 bar of absolute pressure in man: effects on bubble formation and pulmonary function. - Jean-Eric Blatteau (Public Library of Science (PLoS), 2013)
Recent advances in submarine rescue systems have allowed a transfer under pressure of crew members being rescued from a disabled submarine. The choice of a safe decompression procedure for pressurised rescuees has been previously discussed, but no schedule has been validated when the internal submarine pressure is significantly increased i.e. exceeding 2.8 bar absolute pressure. This study tested a saturation decompression procedure from hyperbaric exposures up to 6 bar, the maximum operating pressure of the NATO submarine rescue system. The objective was to investigate the incidence of decompression sickness (DCS) and clinical and spirometric indices of pulmonary oxygen toxicity. Two groups were exposed to a Nitrogen-Oxygen atmosphere (pO2 = 0.5 bar) at either 5 bar (N = 14) or 6 bar (N = 12) for 12 h followed by 56 h 40 min resp. 60 h of decompression. When chamber pressure reached 2.5 bar, the subjects breathed oxygen intermittently, otherwise compressed air. Repeated clinical examinations, ultrasound monitoring of venous gas embolism and spirometry were performed during decompression. During exposures to 5 bar, 3 subjects had minor subjective symptoms i.e. sensation of joint discomfort, regressing spontaneously, and after surfacing 2 subjects also experienced joint discomfort disappearing without treatment. Only 3 subjects had detectable intravascular bubbles during decompression (low grades). No bubbles were detected after surfacing. About 40% of subjects felt chest tightness when inspiring deeply during the initial phase of decompression. Precordial burning sensations were reported during oxygen periods. During decompression, vital capacity decreased by about 8% and forced expiratory flow rates decreased significantly. After surfacing, changes in the peripheral airways were still noticed; Lung Diffusion for carbon monoxide was slightly reduced by 1% while vital capacity was normalized. The procedure did not result in serious symptoms of DCS or pulmonary oxygen toxicity and may be considered for use when the internal submarine pressure is significantly increased.